HUBUNGAN FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGETAHUAN PERIKSA PAYUDARA SENDIRI (SADARI) DI DESA PIPITAN KECAMATAN WALANTAKA KOTA SERANG TAHUN 2020 - Nadya Switing Asmara (2020)
Background: Breast cancer is one of the leading causes of death in women in the world and in Indonesia with a mortality rate of 13 from 100.000 women. The high mortality rate of breast cancer is due to the late diagnosis of breast cancer which can be caused by a lack of knowledge and understanding of breast cancer and early detection of breast cancer. Regular breast self-examination is the most cost-effective methods for early detection of breast cancer. This study aims to analyze the factors affecting to the level of knowledge of breast self-examination (BSE) in Pipitan Village, Walantaka District, Serang City in 2020. Methods: This study is an observational analytic study with a cross-sectional design using online questionnaires for data collection on October 2020 in Pipitan Village. The sample of this study were 108 respondents. Results: Based on the results of the study, 49 (45.4%) respondents had a low level of knowledge and 59 (54.6%) respondents had a high level of knowledge. The results of the Chi Square analysis showed a significant relationship between exposure to information media (p-value 0.000) with the level of knowledge of breast self-examination (BSE). There was no significant relationship between age (p-value 0.438), the level of education (p-value 0.435) and employment (p-value 0.300) with the level of knowledge of breast self-examination (BSE). Conclusion: There was a significant relationship between age exposure to information media with the level of knowledge of breast self-examination (BSE) (p-value 0.000) . Keywords: Breast Cancer Breast Self Examniation (BSE), Knowledge Level.